LC-MS/MS method for detecting trace levels of aflatoxin B1 in cultivated cannabis from Republic of North Macedonia - Pavel Mishevski; Tanja Petreska Ivanovska; Zoran Zhivikj; Lidija Petrushevska-Tozi; Anita Najdenkoska; Maja Mincheva (Makedonsko Farmacevtski Bilten)
This study describes a sensitive liquid chromatography-tandem mass spectrometry (LC-MS/MS) method for detection and quantification of aflatoxin B1 in dried cultivated cannabis flowers from R.N. Macedonia. Aflatoxin B1, a highly carcinogenic mycotoxin produced by Aspergillus species, poses significant health risks, particularly in agricultural products such as cannabis, where contamination levels must be carefully monitored. Traditional methods for detection have difficulties due to the complex matrix of cannabis, which is rich in phytocannabinoids and other bioactive compounds. Therefore, a matrix-matched calibration approach was used and high sensitivity and specificity of the applied LC-MS/MS method were achieved. Validation of the method demonstrated excellent linearity (R²=0.999), precision (CV% < 20%), and recovery rates between 103-112%. When applied to twelve dried flower samples of cannabis cultivated in the Republic of North Macedonia, the method accurately quantified аflatoxin B1 within permitted level (< 2 µg/kg) set by the European Pharmacopoeia. This validated approach confirmed adherence of the investigated samples to the accepted safety standards respecting aflatoxin B1 and could be used as a reliable tool for aflatoxin B1 determination in cannabis production.